DIMENSI ETIKA BISNIS DALAM PELAYANAN KESEHATAN BERDASARKAN PRINSIP-PRINSIP BIOETIKA - Indriani, Dini; Suryana, Deny; Putra S, Fardani; Yuni, Penty; Redjeki, Finny (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the role of business ethics and bioethics in the health care sector, and how bioethical principles can be a moral basis for implementing business ethics. The method used is a literature study, by analyzing various theories and previous studies related to the application of bioethical principles, such as autonomy, beneficence, non-maleficence, and justice, in business practices in the health care sector. The results of the study indicate that business ethics helps health institutions such as hospitals to not only pursue profits, but also provide fair, honest, and responsible services to patients. The application of bioethical principles can form a business ethics policy that supports the quality of health services that are fair, transparent, and responsible. These principles help health institutions ensure patient welfare, respect their rights, and pay attention to social responsibility. The integration of business ethics with bioethics allows hospitals and health facilities to not only focus on financial profit, but also on services that are oriented towards moral values and sustainability. This study makes an important contribution to the development of ethics policies in the health care sector.